Kompetensi Menyusun Rencana Pelaksanaan Pembelajaran (RPP) melalui Bimbingan Berkelanjutan pada Guru Taman Kanak-kanak Masjid Agung Lampung Selatan - Munawaroh, Munawaroh (STKIP PGRI Bandar Lampung, 2020)
The problem found is the low ability of teachers to prepare lesson plans in accordance with adherence to process standards. Meanwhile, one of the teacher's duties is to plan learning well in order to achieve maximum learning objectives. The purpose of this study was to improve the ability of teachers to prepare a Learning Implementation Plan (RPP) through continuous guidance at TK Masjid Agung Lampung Selatan. The results showed that in the first cycle the teacher's ability reached a score of 37 or reached 52% and the second cycle reached a score of 68 or reached 95%. Thus, the ability to compile a Learning Implementation Plan (RPP) can be improved through continuous guidance to the Kindergarten Teachers of the Great Mosque of South Lampung.